The Silent Sufferers: Health Consequences Of Women’s Work In Wayanad’s Agricultural Fields - Jitha C, Jitha C; N. Taibangnganbi, N. Taibangnganbi (Journal of Neonatal Surgery, 2025)
Women employed in Indian agriculture face significant health challenges, including musculoskeletal pain due to physically demanding work and limited healthcare access. This study aims to evaluate the prevalence of musculoskeletal pain, determine contributing factors, and analyze healthcare-seeking behaviour among female agricultural workers in Wayanad, India. A structured questionnaire was employed to conduct a cross-sectional study among a sample of 100 female farm labourers. The study found that 60% of people experienced musculoskeletal discomfort. Factors such as lifting, bending, and repetitive tasks at work, as well as age, education, income, and access to healthcare, were found to be important influences on musculoskeletal pain. Interestingly, only 40 % of those with musculoskeletal pain sought medical help, primarily due to obstacles like lack of transportation and limited availability of healthcare providers. Musculoskeletal pain is a significant health concern that impacts female agricultural workers in Wayanad, India. In order to reduce musculoskeletal discomfort and improve the likelihood of seeking healthcare in this group, it is crucial to provide interventions that specifically address work-related issues, sociodemographic factors, and access to healthcare